Correction: Association between nutritional level, menstrual-related symptoms, and mental health in female medical students. - Keiko Fukushima; Noritoshi Fukushima; Hiroki Sato; Jinko Yokota; Keiko Uchida (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0235909.].